The shadow of the past: Convergence of young and old South American desert lizards as measured by head shape traits - Aguilar Puntriano, César (2018)
Convergence is a pervasive phenomenon in the Tree of Life, and evolution of similar phenotypes sharing the same environmental conditions is expected in phylogenetically closely related species. In contrast, contingent factors are probably more influential in shaping phenotypic diversity for distantly related taxa. Here, we test putative convergent evolution of lizard head morphologies among relatively closely related desert dwelling Liolaemus species, and the very distantly related Ctenoblepharys adspersa. We estimated a multilocus time-calibrated phylogeny of 57 species of South American liolaemus lizards, based on seven molecular markers. We collected head shape data for 468 specimens, and used three phylogenetic comparative methods (SURFACE, CONVEVOL, and WHEATSHEAF index) to test for and estimate the strength of convergence. We found strong evidence for convergence among Pacific desert lizard C. adspersa, Liolaemus audivetulatus, Liolaemus insolitus, Liolaemus poconchilensis, Liolaemus stolzmanni, and a candidate species (Liolaemus “Moquegua”). Our results suggest that, despite the long divergence and phylogenetic distance of C. adspersa with respect to convergent Liolaemus species, natural selection was probably more important than historical contingency in shaping phenotypic evolution in these desert lizards.